Normal Predicted Values of CT Indices Reflect Emphysematous Alterations in the Lung - Suzuki, Koji; Matsubara, Hiroaki; Oguma, Tsuyoshi; Mori, Masaaki; Yamaguchi, Kazuhiro; Koda, Eiichi; Soejima, Kenzo; Inoue, Takashi; Shimada, Hisato (Nihon Kyōbu Shikkan Gakkai zasshi, 1997)
In order to obtain normal values and 95% confidence limits of various CT indices, healthy adult subjects with no history of smoking (n=36) underwent CT scanning under a variety of conditions. By then applying the normal limits thus obtained to CT images of COPD patients (n=45), we examined the sensitivity for detecting abnormal emphysematous changes in the lung fields. To measure emphysematous alterations, we used the average value of lung CT densities (ROI), the maximally appearing value in a CT histogram (Hist. Peak), the relative area with low CT densities below -910 HU (%LDA) and the total cross-sectional area (Area) in each lung section. Regardless of the section thickness (10mm or 1mm), the lung volume level at which the breath was held or the site from which CT images were taken (upper, middle or lower lung field), no significant correlation was observed between the CT indices associated with emphysematous changes and the subjects' age. This allowed us to define, independently of the subjects' age, normal values and 95% confidence limits for the CT indices. Among the CT indices surveyed, %LDA was found to be the most sensitive indicator for detecting emphysematous abnormalities. In so far as the extent of emphysema may be determined by lung CT density, classical CT images of 10-mm section thickness appear to have a sufficiently high sensitivity for the detection of emphysematous abnormalities, such that high-resolution CT may be unnecessary.